Physical and chemical properties of unground palm oil fuel ash mortars incorporating Nano-SiO2 - Noorvand, Hossein (2013)
Abstract: Palm oil fuel ash (POFA) is an abundant agro-waste material obtained from palm oil process. The produced POFA in the mills has large particle size and porous structure which adversely affects the microstructure and pozzolanic reactivity of cementitious mixes, thus grinding process is suggested which can be considered as a physical treatment for morphology of original sized POFA. However, the purpose of this study was to overcome the detrimental effect of morphology of unground POFA (UPOFA) on cement mixtures by incorporation of small amount of nanosilica (NS). In particular, this study was aimed to investigate the effect of 0.5-1.5% NS on the physical and chemical properties of hardened cement mortars containing 10-30% UPOFA. Flowability of fresh samples, and mechanical properties (studied by compression and UPV tests) and microstructural changes (investigated by water absorption, permeable void ratio and SEM tests) of hardened mortars at 7, 28 and 90 days were examined to determine the physical properties of mixes. Furthermore, to trace the chemical composition changes of UPOFA cement mortars with and without NS, X-Ray difraction analysis (XRD) was carried out at 7 and 28 days, and thermo gravimetric analysis (TGA) was conducted at 90 days. The results revealed incorporation of NS compensated the adverse effect of UPOFA on the ow ability, mechanical properties and microstructure of mortars. Admixing only 0.5% NS increased the compressive strength of UPOFA by 11% higher than control sample at 28 days. Besides, incorporation of 0.5% NS augmented the replacement level of UPOFA up to 20% with almost comparable strength to control mortar. Microstructural studies indicated that admixing NS caused remarkable improvement in the porosity and density microstructure of the UPOFA mixes. Significant enrichment within ITZ microstructure of mixes was also observed from SEM images. Moreover, XRD pattern indicated that incorporating NS enhanced pozzolanic reactivity of UPOFA mortars which could further improve the density of matrix. However, no noteworthy enhancement in the compressive strength of UPOFA mortars with NS was observed at 90 days which was also verified by analyzing the CH content using TGA test. It was also observed that lower amount of NS was more effective at enhancing the properties of UPOFA mortars in the course of hydration.